Perceptions and attitudes of secondary school students in Kwazulu-Natal towards virginity testing - Myra Taylor; Siyabonga B Dlamini; Reshma Sathiparsad; Champaklal Jinabhai; Hein de Vries (AOSIS, 2007)
This study describes the prevalence of virginity testing (VT) amongst rural secondary school students in KwaZulu-Natal (KZN), compares the attitudes of students of both sexes to VT, the differences in attitudes between girls who would/would not undergo such testing, and explores the relationship between risky sexual behaviour and girls who underwent virginity testing. Opsomming Hierdie studie beskryf die voorkoms van maagdelikheidstoetsing (MT), by plattelandse sekondêre skoolleerders in KwaZulu-Natal en vergelyk die houdings van leerders van beide geslagte in verband met MT, die verskille in houdings tussen dogters wat sodanige toetsing sal/nie sal ondergaan nie, en verken die verhouding tussen dogters wat maagdelikheidstoetsing ondergaan het en riskante seksuele gedrag. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.